Xavier Zubiri's open materialist realism and Ignacio Ellacuría's philosophy of historical reality - Samour, Héctor (2022)
The article analyzes the main arguments of zubirian philosophical thought since the interpretation of Ignacio Ellacuría to clarify the way in which his metaphysical, anthropological, and epistemological theses are assumed in the construction of the conception of historical reality and in the idea of the political and liberating function of philosophy